Implementasi Kegiatan Pemberdayaan Usaha Mikro "Kepong Bakol" Kubu Raya pada Keunggulan Komparatif UMKM - Pratiwi, Windi; Basri, Muhammad; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study was carried out in a setting in West Kalimantan's Kubu Raya Regency. This study's goals were to identify: Implementation of the Kubu Raya "Kepong Bakol" Micro Enterprise Empowerment Activities in Increasing Comparative Advantage in Kubu Raya. This study employs a qualitative methodology and a case study design. With 7 informants, including 1 key informant and 6 main informants, data was collected using interview, observation, and documentation procedures. According to the research, the "Kepong Bakol" Kubu Raya Micro Enterprise Empowerment Activities were carried out during the empowerment stage. The planning, execution, mentoring, assessment, and follow-up phases of micro business empowerment efforts. Data gathering, need analysis, activity preparation, and cross-sector collaboration are all part of planning. The three accesses of access to money, access to human resource development, and access to marketing are used to carry out the implementation process.